Counter-Linguistic Strategies through Interactive Storytelling to Reduce Slang Vocabulary Mimicry in Early Childhood: - Amdira Diska Al Rinsah; Suharti Suharti; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This descriptive qualitative study examines the effectiveness of counter-linguistic strategies implemented through interactive storytelling to address the imitation of age-inappropriate slang among early childhood students driven by massive digital media exposure. Data gathered through observations, interviews, and documentation reveal that creative narratives featuring polite characters effectively motivate children to adopt correct diction naturally. The two-way interaction inherent in storytelling allows children to clarify the meanings of slang terms encountered on social media, while the repetitive use of positive vocabulary within the narrative helps internalize politeness values without being preachy. The results demonstrate that this strategy successfully reduces slang usage by replacing it with more communicative and polite alternatives. The success of this intervention relies heavily on the teacher's creativity in weaving target vocabulary into engaging plots, leading children to voluntarily switch to more respectful language in their daily interactions, thereby fostering better character development and linguistic etiquette.